PENERAPAN METODE FULL COSTING DALAM PERHITUNGAN HARGA POKOK PRODUKSI SEBAGAI DASAR PENETAPAN HARGA JUAL (STUDI KASUS UMKM SUSU) - Eva Wany (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
UMKM Cow Milk Abah Taslim is a micro business unit that focuses on manufacturing beverage products, namely cow's milk drinks. Unfortunately, currently in determining the calculation of the cost of production, the Abah Taslim Cow Milk UMKM still does not use the applicable accounting standards and has not recorded and taken into account all incoming and outgoing costs in producing goods. The written research focuses on the application of the full costing method. This written research aims to find out the difference in the cost of production determined by the UMKM Abah Taslim Cow Milk and that determined by the full costing method, as well as the selling price determined by the MSME Abah Taslim Cow Milk with that determined by the cost plus pricing method. Qualitative methods are applied to written research. collect information for written research through methods such as observation, interviews, and documentation. The findings of the written study show that MSMEs still calculate production costs using a straightforward method that generates IDR 5,357 per bottle. The price per bottle is Rp. 7,163 in calculations carried out using the full costing technique. Using the cost plus pricing approach to obtain the selling price, the yield per bottle is Rp. 8,500. MSMEs still do not estimate the desired profit when determining the selling price of their products.